Letter : Assistance for Spain - Smith, Fred A.
030-0101-001 AMALGAMATED ENGINEERING UNION General Office: 110, PECKHAM ROAD, LONDON, S.E.15 FRED. A. SMITH, General Secretary, to whom all Communications should be addressed Our Ref.: FAS/MG. Your Ref.: WMC/FC/EK/1546. Telephone: RODNEY 5294 (3 lines) Telegraphic Address: "EDIFYING, PECK, LONDON " 5th August, 1938. The General Secretary, Trades Union Congress, Transport House, Smith Square, LONDON. S.W.1. Dear Sir, ASSISTANCE FOR SPAIN: I am in receipt of your letter of the 4th instant relative to the above subject, which will be placed before my Executive Council as early as possible. Yours faithfully, Fred A Smith GENERAL SECRETARY: 292/946/30/101